Effects of Citrus Fruit Juices and Their Bioactive Components on Inflammation and Immunity: A Narrative Review - Miles, Elizabeth A.; Calder, Philip C. (Frontiers in Immunology, 2021)
The immune system provides defence to the host against pathogenic organisms. A weak immune system increases susceptibility to infections and allows infections to become more severe. One component of the immune response is inflammation. Where inflammation is excessive or uncontrolled it can damage host tissues and cause pathology. Limitation of oxidative stress is one means of controlling inflammation. Citrus fruit juices are a particularly good source of vitamin C and folate, which both have roles in sustaining the integrity of immunological barriers and in supporting the function of many types of immune cell including phagocytes, natural killer cells, T-cells and B-cells. Vitamin C is an antioxidant and reduces aspects of the inflammatory response. Important bioactive polyphenols in citrus fruit juices include hesperidin, narirutin and naringin. Hesperidin is a glycoside of hesperetin while narirutin and naringin are glycosides of naringenin. Hesperidin, hesperetin, naringenin, naringin and narirutin have all been found to have anti-inflammatory effects in model systems, and human trials of hesperidin report reductions in inflammatory markers. In humans, orange juice was shown to limit the post-prandial inflammation induced by a high fat-high carbohydrate meal. Consuming orange juice daily for a period of weeks has been reported to reduce markers of inflammation, including C-reactive protein, as confirmed through a recent meta-analysis. A newly emerging topic is whether polyphenols from orange juice have direct anti-viral effects. In summary, micronutrients and other bioactives present in citrus fruit juices have established roles in controlling oxidative stress and inflammation and in supporting innate and acquired immune responses. Trials in humans demonstrate that orange juice reduces inflammation; its effects on innate and acquired immunity require further exploration in well-designed trials in appropriate population sub-groups such as older people.